The effect of parental education on child and adult health in Zambia: A regression discontinuity analysis - Daka, Lincoln (University of the Witwatersrand, Johannesburg, 2024)
This thesis expands upon and enhances existing research in the field of health economics. The thesis consists of three separate yet interrelated chapters that examine the effect of education on key demographic variables: child health, fertility and HIV/AIDS in Zambia, three key factors affecting the progress of development in Africa. The endogeneity problem is present in all of the three empirical papers examined. To circumvent this endogeneity problem and establish a credible causal effect, we explore the impact of Zambia’s 2002 Universal Free Primary Education (UFPE) policy which created an exogenous source of variation in education as a quasi – experiment. The three substantial empirical studies, employ the same econometric methodology, a Regression Discontinuity Design (RDD), whose appealing feature is local randomisation. This characteristic has distinguished the method from other evaluation methods in terms of estimating unbiased treatment effects. Another advantage of the fuzzy Regression Discontinuity design is that it can account for the endogeneity of the treatment variable. The utilisation of the fuzzy Regression Discontinuity design is a valuable contribution in all of the research. Furthermore, every chapter makes a unique contribution within its respective sector. We outline Zambia’s Universal Free Primary Education (UFPE) Policy and also present the Regression Discontinuity Design methodology framework. We find significant causal impacts of maternal education on child health measured by height-for-age, weight-for-height and Weight-for- age. The findings also indicate that maternal education is associated with a reduction in the prevalence of stunting and underweight and no effect wasting contrary to other research. We present evidence of the several mechanisms by which maternal education impacts child health. The results of our study indicate that a greater level of maternal education exerts a beneficial influence on child health through the postponement of marriage, the reduction in total fertility, and the delay in the age of first childbirth and sexual debut. Additionally, we have discovered indications of positive assortative mating. Furthermore, education empowers moms by facilitating their access to information via television and newspapers, equipping them with knowledge about the ovulation time, and helping them to make well-informed decisions regarding contraceptive techniques. Conventional wisdom posits that decreased fertility may indicate the presence of “superior quality” children and increased rates of survival for both mother and child. Can education serve as a catalyst for decreasing fertility rates in developing nations? We find that female education reduces iv | P a g e the number of children ever born. We present evidence of the reduction in total fertility as a result of female education. We also show that female schooling reduces the preferred number of children and increases the age at first birth. We find that female schooling affects fertility through age at first sex and marriage, literacy, assortative mating and the knowledge effect. There is no evidence to suggest that female schooling has a major impact labour market participation. We present evidence of the heterogeneous impacts of a mother’s education based on “poor versus wealthy” criterion, whether rural/urban status, region and religion. We also present evidence of the effect of female education on the HIV seroprevalence status, number of sexual partners and knowledge of HIV transmission mechanisms. We show that female education lowers HIV seroprevalence status, decreases the number of sexual partners and increases HIV knowledge. Our research suggests that educated women are more likely to have a deep and detailed understanding of HIV. Lastly, we present evidence of the heterogeneous effects of female education by household status on HIV related outcomes.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Regression Discontinuity Design; Universal Free primary Education Maternal Education Child health Fertility HIV/AIDS; SDG-4: Quality education; SDG-3: Good health and well-being